MODEL STOKASTIK RANTAI MARKOV EMPAT STATUS PADA PENENTUAN NILAI HIDUP PELANGGAN - Dony Permana (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2017)
Customer Lifetime Value, familiar as CLV is valuability a customer in marketing system. High CLV has a meaning that the customer will bring in a big return for a firm. CLV is determined by some factors, as retention rate, acquisition rate, some costs, product price, and interest rates. Markov Chain is one of model that used to determine CLV. In Markov Chain, a customer is assumed some state. Transition inter states are assumed Markovian. Here, we make CLV model using Markov Chain with four states. There are four type of model that have four states. Each type have different transition chart and of course have different probability transition matrix. Here, we describe every type of CLV model using Markov Chain.